PENGARUH MODEL PEMBELAJARAN PASAR TEHADAP HASIL BELAJAR PPKn SISWA KELAS VIII SMPN 1 PUSAKO KECAMATAN PUSAKO KABUPATEN SIAK - Lia Permana; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low student learning outcomes of PPKn at SMPN 1 Pusako. The formulation of the problem in this study is